Edukasi Makanan Pendamping ASI sebagai Upaya Pencegahan Stunting pada Ibu Balita Usia 6-24 Bulan - Tyaningsih, Sulis; Cahyaningrum, Etika Dewi; Murniati, Murniati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Complementary foods are given to infants age 6–24 months to supplement nutritional needs that are not met by breast milk alone. Proper feeding can prevent stunting, which is a condition of growth failure with height below the standard for age. Objective: This activity aims to increase the knowledge of mothers of toddlers regarding the provision of complementary foods as a measure to prevent stunting. Method: Health education was delivered to 20 mothers of toddlers using lectures, discussions, and demonstrations supported by PowerPoint presentations and pocket books. Each session began with the presentation of material, followed by a question-and-answer segment to enchance participants’ understanding, and concluded with hands-on practice to apply what they had learned. The activities were conducted over three meetings between April and May 2025, focusing on improving mothers’ knowledge and skills in maintaining their children’s health and development. Result: The evaluation results showed that prior to education, the majority of participants had a good level of knowledge (9 people, or 45%), while 7 people (35%) had an adequate level of knowledge, and 4 people (20%) had a poor level of knowledge. After education, all 20 participants achieved a good level of knowledge (100%), with an average increase in knowledge scores from 72.2 to 90.38. Conclusion: These findings prove that complementary feeding education is effective in increasing mothers' knowledge and supporting efforts to prevent stunting.